Investigating the Effect of Perceived Workplace Climate on the Well-being of Academic Staff at Makerere University - Mbabazi, Annet; Balojja, Tom Darlington (Interdisciplinary Journal of Education, 2023)
The purpose of this study was to analyse how workplace climate affects the well-being of academic staff at Makerere University. The study was prompted by the reportedly persistent ill-being of academic staff at Makerere University in the recent past. The study followed a concurrent design, where the quantitative approach partook a cross-sectional survey design and the qualitative used a phenomenological survey design. Self-administered questionnaires were used to collect data from a sample of 383 academic staff and interviewing four heads of departments and four academic staff distributed in three colleges and one school. The respondents were selected using stratified random sampling and purposive sampling. The qualitative data was analysed through thematic and content analysis inductively. Later, both data sets converged during interpretation to obtain common implications. Qualitative findings indicated participants had varying perspectives on the workplace climate for instance, participants' voices ranged from challenging to supportive and adaptable, stressful and rewarding. This implied that such mixed feedback from different voices had different implications and consequences for individual participants. Quantitative data were analysed using descriptive statistics, inferential statistics, (r = .529, n = 286, p = .000> 0.05), and multiple analysed by linear regression R2 = 0.281, p =0,000 >.05). F statistic = 37.550, p= 0.00>0.05, Beta= 0.350, p= 0.00>0.05. The findings indicated a statistically significant positive relationship and effect between well-being and workplace climate in terms of work pleasure, job rewards, and career growth opportunities.